Alterations in lipid homeostasis of mouse dorsal root ganglia induced by apolipoprotein E deficiency: a shotgun lipidomics study - Cheng, Hua (2007)
One of the fundamental goals of lipidomics research is to identify the linkage of an individual gene with a given lipidome, thereby revealing the role of that gene in lipid metabolism, transport, and homeostasis. In this study, we have identified four apolipoprotein E (apoE)-induced alterations in the lipidome of mouse dorsal root ganglia (DRG) through utilizing the technology of shotgun lipidomics. First, apoE mediates sulfatide mass content in mouse DRG, which is comparable to its role in the CNS. Second, apoE contributes to galactosylceramide and ceramide homeostasis in mouse DRG. Third, apoE significantly modulates cholesterol levels in mouse DRG. The latter two functions of apoE are distinct from those in the CNS. Finally, mice null for apoE have dramatically less triacylglycerol mass content in DRG which are opposite to the effects observed in the peripheral organs and vascular system. Collectively, this study identifies the specific alterations in the DRG lipidome induced by apoE knockout and suggests the potential roles of apoE in lipid transport and homeostasis in a tissue specific manner, thereby providing insights into the biochemical mechanisms underlying the functions of apoE in the PNS.